Épocas e métodos de manejo de aveia preta na produtividade de milho - Sgarbossa, Maicon (2020)
The amount of straw in the field is a fundamental requirement in the no-tillage system. The black oatis the main cover crop cultivated before the summer crops, such as maize and soybeans in Southern Brazil. The periodsand the straw managementare essential for the development of the next crop season in the field because the time that theresidues stayon the soil and the seeder plantability depend on them. Considering that, the aim of this work was to evaluate methods and different periodsof oat straw management and its implications for plantability, development, and productivity of themaize crop, duringtwo growing seasons. The experiment was carried outat the experimental area of the Universidade Tecnológica Federal do Paraná, Campus Pato Branco –PR. The soil was classified as a Typic Hapludox, with a very clayeytexture. The treatments consisted of a combination of three oat strawmanagement(crushed, rolled, and desiccated) and four periods (0, 10, 20, and 30 days before sowing the maize). Soil resistance to penetration, oat dry matter, seed depositiondepth, soil area mobilized, index of emergency speed, longitudinal distribution of plants, emergence operation, initial and final plant population, initial and final height, stem diameter, ear insertion height, ear diameter, ear length, number of rows of grains perear, number of grains per row, prolificacy, thousand-grain mass and productivity were evaluated. The data were submitted to analysis of variance and, if a significant difference was found (p≤0.05), the means of the oat straw management were compared by the Tukey test (p≤0.05), while for the factor period, polynomial regression analysis was adopted, and the models were selected considering the greater R2and the significance (p≤0.05) of equation parameters. The principal component analysis was performedto identify the variables that better explain the data variability. The management of oat plants carried out 30 days before the sowing of maize provides a higher rate of emergence of the crop. The oat strawmanagementand periodsof management of oat plants do not affect the seed depositiondepth, soil areamobilized, the plant height, number of rows per ear, prolificacy, andmaizeproductivity.